Analisis Hukum Peran Artificial Intelligence (AI) dalam Penyelesaian Sengketa Bisnis di Era Digitalisasi - Yamani Naufal; Dian May Syifa; Bambang Sutiyoso (AHKAM, 2026)
Although the role of Artificial Intelligence (AI) in dispute resolution has received considerable attention in previous studies, research that specifically analyzes its legal implications using a comprehensive theoretical framework remains limited. This study aims to analyze the role of AI in business dispute resolution in the digital era and to examine its legal implications through a normative approach. This study used a normative legal method with a conceptual approach and a statutory approach. The research data consisted of secondary data collected through literature study and analyzed using descriptive-analytical techniques. The results show that AI is able to improve efficiency, speed, and access to justice in dispute resolution, both through litigation and nonlitigation mechanisms, such as Online Dispute Resolution (ODR). However, the use of AI still faces fundamental challenges, including a lack of algorithmic transparency, unclear accountability, the risk of bias, and issues related to human rights protection. From the perspective of Gustav Radbruch’s theory of legal purposes, the use of AI shows a tension between justice, legal certainty, and utility. AI tends to excel in the aspect of utility, but it has the potential to reduce justice and create legal uncertainty if not supported by adequate regulation. These findings provide a theoretical contribution by integrating studies of technology law and Radbruch’s theory as an analytical framework for AI-based dispute resolution. The conclusion of the study emphasizes that the use of AI in business dispute resolution requires comprehensive regulation and human oversight so that its implementation remains fair, transparent, and accountable.